53.9k views
4 votes
3 (bx - 2ab) = b (x - 7a) + 3ab solve for x

User Jarnal
by
6.1k points

2 Answers

4 votes
3(bx - 2ab) = b(x - 7a) + 3ab
<=> 3bx - 6ab = bx - 7ab + 3ab
<=> 3bx - bx = 6ab - 7ab + 3ab
<=> 2bx = 2ab
<=> x = a
User ZZA
by
6.3k points
4 votes

Answer:

The value of x = a.

Explanation:

Consider the provided equation.

3 (bx - 2ab) = b (x - 7a) + 3ab

Use the distributive property: a(b+c)=ab+ac

3bx - 6ab = bx - 7ab + 3ab

Now add the like variable.

3bx - 6ab = bx - 4ab

Subtract bx and add 6ab on both sides.

3bx - 6ab - bx + 6ab = bx - bx - 4ab + 6ab

2bx = 2ab

Divide both the side by 2b.

x = a

Hence, the value of x = a.

User Ben Kirby
by
5.8k points